Electrocatalyst and application thereof in oxidation of biomass alcohol terminal hydroxyl
By designing a gold-palladium-copper ternary metal electrocatalyst, using its core-shell structure and specific molar ratio, the problem of insufficient efficiency and selectivity of traditional biomass alcohol terminal hydroxyl oxidation technology under normal temperature and pressure is solved, and biomass alcohol is realized efficient conversion and highly selective product generation.
Patent Information
- Application Number
- CN202411623499.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional biomass alcohol-terminal hydroxyl oxidation technology is difficult to efficiently and selectively convert biomass alcohol-terminal hydroxyl groups under normal temperature and pressure, and there is a problem of toxicity of catalysts by COads.
Using gold-palladium-copper ternary metal electrocatalyst, through the design of core-shell structure, a high-stability and high-activity catalyst is constructed using the molar ratio of gold, palladium and copper to be 1:1:1 to construct a high-stability and high-activity catalyst for biomass alcohol ends. Hydroxygenation reaction.
Under normal temperature and pressure, high-efficiency oxidation of glycerol, 1,2-propylene glycol and ethylene glycol were achieved, and glyceric acid, lactic acid and acetic acid were produced respectively, and the catalyst showed high selectivity and stability.
Smart Images

Figure CN119465286A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalytic oxidation of biomass alcohol, and specifically relates to an electrocatalyst and use thereof in oxidation of terminal hydroxyl groups of biomass alcohol. Background Art
[0002] Biomass polyols are mainly derived from biomass resources such as vegetable oils, sugars, and cellulose. They have the advantages of wide sources, renewability, and sustainability. They are widely used in the synthesis of bio-based materials and play an important role in the fields of food and medicine. The structure of biomass polyols contains carbon chains and polyhydroxyl functional groups. The electrocatalytic oxidation process involves multiple parallel reactions and serial reactions, and there are many products. Designing efficient catalysts to promote the activation of hydroxyl groups while avoiding the breakage of C-C bonds, thereby generating a single product with high selectivity, is one of the main challenges currently faced by this reaction.
[0003] Among many precious metal electrocatalysts, Pd-based electrocatalysts show excellent performance in the electrocatalytic oxidation reaction of biomass alcohol. Compared with traditional Pt-based electrocatalysts, Pd is cheaper and more abundant, and has gradually become a substitute for Pt-based catalysts. Studies have shown that when Pd-based electrocatalysts are used in the electrocatalytic reaction of biomass alcohol, only a small number of sites (steps and kink active sites with low coordination numbers) will adsorb the reaction intermediate CO ads , has stronger anti-poisoning ability, but CO ads The poisoning effect of Pd remains a serious problem. Adding a second component metal to the catalyst is one of the common strategies to optimize the activity of the electrocatalytic oxidation reaction of s-biomass alcohols. In Pd electrocatalysts, other metals are introduced to construct d-band hybridization, thereby changing the selectivity and catalytic activity of the products, and can also effectively reduce the association with CO and enhance the catalytic stability. Wang et al. used palladium-selenium nanowires of different crystalline phases to study the activation potential of ethylene glycol oxidation to C1 and C2 products, and confirmed that Pd-based catalysts are beneficial to the energy barrier of CO* oxidation and the adsorption capacity of intermediates (Small, 2024, 20, 2403448). Summary of the invention
[0004] The present invention aims to solve the problems in the traditional biomass alcohol terminal hydroxyl oxidation technology, and aims to provide a new method for biomass alcohol electrocatalytic oxidation, so as to realize the green and efficient conversion of biomass alcohol terminal hydroxyl groups under the reaction conditions of normal temperature and pressure. The problem to be solved is to prepare a highly stable and highly active biomass alcohol electrocatalyst, which can be used for electrocatalytic oxidation of glycerol to prepare glyceric acid, 1,2-propylene glycol to prepare lactic acid, and ethylene glycol to prepare acetic acid in potassium hydroxide solution at normal temperature and pressure.
[0005] In order to achieve the above technical purpose, the technical solution of the present invention is as follows:
[0006] The invention provides a gold-palladium-copper ternary metal electrocatalyst. The catalyst consists of gold, palladium and copper, wherein palladium is used as an active component, gold is used as a core and a palladium-copper alloy is used as a shell to form a core-shell structure; the molar ratio of gold, palladium and copper in the catalyst is 1:1:1.
[0007] The preparation method of the catalyst is as follows:
[0008] Add polyvinyl pyrrolidone, ascorbic acid and potassium bromide to ethylene glycol, stir and heat to a certain temperature, then drop a copper sulfate pentahydrate aqueous solution, react for a period of time after the dropwise addition (copper is completely reduced and the solution turns brown), then drop a mixed solution A to continue the reaction, the mixed solution A is a mixed solution of chloroauric acid trihydrate and chloropalladic acid; after the reaction, stop stirring and naturally cool to room temperature, collect the product by centrifugation or filtration, and wash the obtained product with anhydrous ethanol and acetone alternately for several times to obtain a washed product;
[0009] Subsequently, the washed product is further washed several times with warm water (to completely remove the polyvinyl pyrrolidone in the catalyst), and the product obtained after washing is a purified catalyst; finally, the purified catalyst is dried to obtain a gold-palladium-copper catalyst; wherein, chloropalladic acid is prepared by mixing palladium chloride and concentrated hydrochloric acid in a molar ratio of 1:2.
[0010] Preferably, the dosage relationship of the ethylene glycol, polyvinyl pyrrolidone, ascorbic acid, potassium bromide, copper sulfate pentahydrate aqueous solution, and mixed solution A is 50-100 mL: 0.3-0.6 g: 2-4 g: 2-4 g: 12-24 mL: 12-24 mL; wherein the concentration of copper sulfate pentahydrate aqueous solution is 11.3 mM; the concentration of chloroauric acid trihydrate in mixed solution A is 22.6 mM, and the concentration of chloropalladic acid is 22.6 mM.
[0011] Preferably, the temperature is raised to 70-90° C., the reaction time after adding the aqueous copper sulfate pentahydrate solution is 0.5-1 h, and the reaction time after adding the mixed solution A is 1-2 h.
[0012] Preferably, the alternating washing is performed 7-8 times, and the washing operation is centrifugal washing, with a rotation speed of 8000-10000 rpm and a centrifugal time of 3-5 min;
[0013] Preferably, the temperature of the warm water is 40°C, the washing is continued for 3 times, the washing operation is centrifugal washing, the rotation speed is 8000-10000rpm, and the centrifugal time is 3-5min; the drying temperature is 40°C and the time is 12h.
[0014] The gold-palladium-copper alloy catalyst is used for the oxidation of terminal hydroxyl groups of biomass alcohols, and the specific application scheme is as follows:
[0015] The prepared gold palladium copper catalyst is mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, 3006 μL in total) to obtain catalyst ink; the catalyst ink is then evenly coated on carbon paper, and after vacuum drying, carbon paper loaded with gold palladium copper catalyst is obtained for anode material. At room temperature and pressure, a three-electrode system is formed with carbon paper loaded with gold palladium copper catalyst as a working electrode, a mercury-mercury oxide electrode as a reference electrode, and a carbon rod as a counter electrode, and an anion exchange membrane is used to separate the positive and negative electrodes. The entire reaction environment is carried out in a saturated nitrogen atmosphere, and an electrochemical workstation is used to apply a constant potential to the electrolyte to achieve the purpose of oxidizing the terminal hydroxyl group of biomass alcohol. The electrolyte is a mixed solution of glycerol and potassium hydroxide, a mixed solution of 1,2-propylene glycol and potassium hydroxide, or a mixed solution of ethylene glycol and potassium hydroxide.
[0016] Preferably, the dosage ratio of the gold palladium copper catalyst to isopropanol is 40 mg: 501 μL; the volume ratio of the deionized water, isopropanol, ethylene glycol and Nafion solution is 20: 5: 3: 2; the dosage relationship of the catalyst ink to the carbon paper is: 70-75 μL per square centimeter of carbon paper. Preferably, the vacuum drying temperature is 40-60°C, and the drying time is 3-4 hours.
[0017] Preferably, in the mixed solution of glycerol and potassium hydroxide, the molar ratio of glycerol to potassium hydroxide is 0.05-0.5 mol:0.5-2 mol; in the mixed solution of 1,2-propylene glycol and potassium hydroxide, the molar ratio of 1,2-propylene glycol to potassium hydroxide is 0.05-0.5 mol:0.5-2 mol; in the mixed solution of ethylene glycol and potassium hydroxide, the molar ratio of ethylene glycol to potassium hydroxide is 0.05-0.5 mol:0.5-2 mol; the flow rate of nitrogen is 100 mL / min, and the applied constant potential is 0.83-1.03 V.
[0018] Beneficial effects:
[0019] The present invention provides a method for electrocatalytic oxidation of terminal hydroxyl groups of biomass alcohols. A noble metal core-shell catalyst is prepared as an anode electrocatalyst by a simple polyol reduction method. By adjusting the atomic ratio between metals, reaction time, reaction potential and other conditions, the conversion rate of polyols and the selectivity to products can be stably controlled. In addition, multiple cycles of chronoamperometric experiments show that the catalyst has high stability and has broad application prospects in the field of electrochemistry. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the Au@PdCu catalyst with an atomic ratio of 1:1:1.
[0021] Figure 2XRD patterns of Au@PdCu catalysts with atomic ratios of 1:1:1, 1:0.5:1, 0.5:1:1, 1:1:0, 1:0:1, and 0:1:1.
[0022] Figure 3 These are CV diagrams of Au@PdCu catalyst atomic ratios of 1:1:1, 11:0.5:1, 0.5:1:1, 1:1:0, 1:0:1, and 0:1:1.
[0023] Figure 4 This is the relationship between product selectivity and substrate conversion rate when the applied potential is 0.93V.
[0024] Figure 5 This is the relationship between the product selectivity and glycerol conversion rate corresponding to catalysts with different atomic ratios when the applied potential is 0.93V.
[0025] Figure 6 This is the relationship between the selectivity and glycerol conversion rate of Au1@Pd1Cu1 catalyst under different reaction potentials when the reaction time is 8h.
[0026] Figure 7 This is a graph showing the relationship between product selectivity, glycerol conversion rate and time when the applied potential is 0.93 V. DETAILED DESCRIPTION
[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0028] It should be understood that the terms described in the present invention are only for describing specific embodiments and are not intended to limit the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art in the art to which the present invention relates.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0030] The chloropalladic acid of this embodiment is prepared by mixing palladium chloride and concentrated hydrochloric acid in a molar ratio of 1:2, which is a well-known method.
[0031] Example 1: An anode catalyst for preparing glyceric acid by electrocatalytic oxidation of glycerol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 1:1:1.
[0032] Weigh 0.6 g of polyvinyl pyrrolidone, 3 g of ascorbic acid and 3 g of potassium bromide, stir and dissolve in 100 mL of ethylene glycol, stir and heat to 80° C.; then add 24 mL of a cupric sulfate pentahydrate aqueous solution (11.3 mM), continue heating and stirring for 0.5 h, then measure 12 mL of a mixed solution of chloroauric acid trihydrate and chloropalladic acid (in the mixed solution, the concentration of chloroauric acid trihydrate is 22.6 mM, and the concentration of chloropalladic acid is 22.6 mM) and add dropwise to the above solution to react for 1 h, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone 7 times (alternating washing is centrifugal washing, the speed is 8000 rpm, and the centrifugation time is 5 min) to obtain the washed product;
[0033] Subsequently, the washed product was washed three times with 40°C warm water (also centrifugal washing, rotation speed 8000rpm, centrifugal time 5min) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst. Finally, the purified catalyst was dried in a vacuum drying oven at 40°C for 12h to obtain a gold palladium copper catalyst, denoted as Au1@Pd1Cu1 catalyst, and its scanning electron microscope image is shown in Figure 1 shown.
[0034] 40 mg of the catalyst prepared in this example was mixed evenly with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, 3006 μL in total) to prepare catalyst ink; then 300 μL of the catalyst ink was evenly coated on carbon paper (coating area was 2×2 cm 2 ), and dried at 40°C in vacuum for 3h. After drying, the carbon paper loaded with the catalyst was obtained, which was used as the working electrode for the electrocatalytic oxidation reaction of glycerol, and mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, the electrolyte was a mixed solution of glycerol and potassium hydroxide, a total of 60mL, wherein the concentration of glycerol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 0.93Vvs RHE, and the reaction time was 8h at room temperature and pressure.
[0035] The product was detected by high performance liquid chromatography and found that the glycerol conversion rate was 59% and the glyceric acid selectivity was 34%. The conversion rate and product distribution diagram are shown in Figure 2. Figure 4 shown.
[0036] Example 2: An anode catalyst for preparing lactic acid by electrocatalytic oxidation of 1,2-propylene glycol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 1:1:1.
[0037] Weigh 0.6 g of polyvinyl pyrrolidone, 3 g of ascorbic acid and 3 g of potassium bromide, stir and dissolve in 100 mL of ethylene glycol, stir and heat to 80° C.; then add 24 mL of a cupric sulfate pentahydrate aqueous solution (11.3 mM), continue heating and stirring for 0.5 h, then measure 12 mL of a mixed solution of chloroauric acid trihydrate and chloropalladic acid (in the mixed solution, the concentration of chloroauric acid trihydrate is 22.6 mM, and the concentration of chloropalladic acid is 22.6 mM) and add dropwise to the above solution to react for 1 h, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone 7 times (alternating washing is centrifugal washing, the speed is 8000 rpm, and the centrifugation time is 5 min) to obtain the washed product;
[0038] Subsequently, the washed product was washed three times with 40°C warm water (also centrifugal washing, rotation speed 8000rpm, centrifugal time 5min) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst. The purified catalyst was dried in a vacuum drying oven at 40°C for 12h to obtain a gold palladium copper catalyst, denoted as Au1@Pd1Cu1 catalyst, and its scanning electron microscope image is shown in FIG. Figure 1 shown.
[0039] 40 mg of the catalyst prepared in this example was mixed evenly with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, 3006 μL in total) to prepare catalyst ink; then 300 μL of the catalyst ink was evenly coated on carbon paper (coating area was 2×2 cm 2 ), and dried under vacuum at 40°C for 3h. After drying, the carbon paper loaded with the catalyst was obtained, which was used as the working electrode for the electrocatalytic oxidation reaction of 1,2-propylene glycol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, the electrolyte was a mixed solution of 1,2-propylene glycol and potassium hydroxide, a total of 60mL, wherein the concentration of 1,2-propylene glycol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 0.93V vs RHE, and the reaction time was 8h at room temperature and pressure.
[0040] The product was detected by high performance liquid chromatography and found that the conversion rate of 1,2-propylene glycol was 51% and the selectivity of lactic acid was 53%. The conversion rate and product distribution were as follows: Figure 4 shown.
[0041] Example 3: An anode catalyst for preparing glycolic acid by electrocatalytic oxidation of ethylene glycol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 1:1:1.
[0042] Weigh 0.6 g of polyvinyl pyrrolidone, 3 g of ascorbic acid and 3 g of potassium bromide, stir and dissolve in 100 mL of ethylene glycol, stir and heat to 80° C.; then add 24 mL of a cupric sulfate pentahydrate aqueous solution (11.3 mM), continue heating and stirring for 0.5 h, then measure 12 mL of a mixed solution of chloroauric acid trihydrate and chloropalladic acid (in the mixed solution, the concentration of chloroauric acid trihydrate is 22.6 mM, and the concentration of chloropalladic acid is 22.6 mM) and add dropwise to the above solution to react for 1 h, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone 7 times (alternating washing is centrifugal washing, the speed is 8000 rpm, and the centrifugation time is 5 min) to obtain the washed product;
[0043] Subsequently, the washed product was further washed three times with 40°C warm water (also centrifugal washing) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst. The purified catalyst was dried in a vacuum drying oven at 40°C for 12 hours to obtain a gold palladium copper catalyst, recorded as Au1@Pd1Cu1 catalyst.
[0044] 40 mg of the catalyst prepared in this example was mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, a total of 3006 μL) to prepare catalyst ink. 300 μL of the catalyst ink was evenly coated on carbon paper (the actual coating area was 2×2 cm 2 ), vacuum dried at 40°C for 3h, and the catalyst-loaded carbon paper was obtained after drying, which was used as the working electrode for the electrocatalytic oxidation reaction of ethylene glycol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, the electrolyte was a mixed solution of ethylene glycol and potassium hydroxide, a total of 60mL, wherein the concentration of ethylene glycol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 0.93Vvs RHE, and the reaction time was 8h at room temperature and pressure.
[0045] The product was detected by high performance liquid chromatography and the conversion rate of ethylene glycol was 72% and the selectivity of glycolic acid was 99%. The conversion rate and product distribution are shown in Figure 2. Figure 4 shown.
[0046] Example 4: An anode catalyst for preparing glyceric acid by electrocatalytic oxidation of glycerol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 1:0.5:1.
[0047] Weigh 0.6 g of polyvinyl pyrrolidone, 3 g of ascorbic acid and 3 g of potassium bromide, stir and dissolve in 100 mL of ethylene glycol, stir and heat to 80° C.; then add 24 mL of a cupric sulfate pentahydrate aqueous solution (11.3 mM), continue heating and stirring for 0.5 h, then measure 12 mL of a mixed solution of chloroauric acid trihydrate and chloropalladic acid (in the mixed solution, the concentration of chloroauric acid trihydrate is 22.6 mM, and the concentration of chloropalladic acid is 11.3 mM) and add dropwise to the above solution to react for 1 h, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone 7 times (alternating washing is centrifugal washing, the speed is 8000 rpm, and the centrifugation time is 5 min) to obtain a washed product;
[0048] Subsequently, the washed product was washed three times with 40°C warm water (also centrifugal washing, rotation speed 8000rpm, centrifugal time 5min) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst, and the purified catalyst was dried in a vacuum drying oven at 40°C for 12h to obtain a gold palladium copper catalyst, recorded as Au1@Pd 0.5 Cu1 catalyst.
[0049] 40 mg of the catalyst prepared in this example was mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, a total of 3006 μL) to prepare catalyst ink. 300 μL of the catalyst ink was evenly coated on carbon paper (the actual coating area was 2×2 cm 2 ), vacuum dried at 40°C for 3h, and the catalyst-loaded carbon paper was obtained after drying, which was used as the working electrode for the electrocatalytic oxidation reaction of glycerol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, and the electrolyte was a mixed solution of glycerol and potassium hydroxide, totaling 60mL, in which the concentration of glycerol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 0.93V vs RHE, and the reaction time was 8h at room temperature and pressure.
[0050] The product was detected by high performance liquid chromatography and the glycerol conversion rate was 54% and the glyceric acid selectivity was 34%. The conversion rate and product distribution were as follows: Figure 5 shown.
[0051] Example 5: An anode catalyst for preparing glyceric acid by electrocatalytic oxidation of glycerol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 0.5:1:1.
[0052] Weigh 0.6g of polyvinyl pyrrolidone, 3g of ascorbic acid and 3g of potassium bromide, stir and dissolve in 100mL of ethylene glycol, stir and heat to 80°C; then measure 24mL of copper sulfate pentahydrate aqueous solution (11.3mM) and add it to the ethylene glycol solution, continue heating and stirring for 0.5h, then measure 12mL of a mixed solution of chloroauric acid trihydrate and chloropalladic acid (in the mixed solution, the concentration of chloroauric acid trihydrate is 11.3mM, and the concentration of chloropalladic acid is 22.6mM) and add it dropwise to the above solution to react for 1h, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone 7 times (alternating washing is centrifugal washing, the speed is 8000rpm, and the centrifugation time is 5min) to obtain the washed product;
[0053] Subsequently, the washed product was washed three times with 40°C warm water (also centrifugal washing, rotation speed 8000rpm, centrifugal time 5min) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst, and the purified catalyst was dried in a vacuum drying oven at 40°C for 12h to obtain a gold palladium copper catalyst, recorded as Au 0.5 @Pd1Cu1 catalyst.
[0054] 40 mg of the catalyst prepared in this example was mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, a total of 3006 μL) to prepare catalyst ink. 300 μL of the catalyst ink was evenly coated on carbon paper (the actual coating area was 2×2 cm 2 ), vacuum dried at 40°C for 3h, and the catalyst-loaded carbon paper was obtained after drying, which was used as the working electrode for the electrocatalytic oxidation reaction of glycerol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, and the electrolyte was a mixed solution of glycerol and potassium hydroxide, totaling 60mL, in which the concentration of glycerol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 0.93V vs RHE, and the reaction time was 8h at room temperature and pressure.
[0055] The product was detected by high performance liquid chromatography and the glycerol conversion rate was 22% and the glyceric acid selectivity was 43%. The conversion rate and product distribution were as follows: Figure 5 shown.
[0056] Example 6: An anode catalyst for preparing glyceric acid by electrocatalytic oxidation of glycerol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 1:1:0.
[0057] Weigh 0.6 g of polyvinyl pyrrolidone, 3 g of ascorbic acid and 3 g of potassium bromide, stir and dissolve in 100 mL of ethylene glycol, stir and heat to 80° C., then add 12 mL of a mixed solution of chloroauric acid trihydrate and chloropalladic acid (in the mixed solution, the concentration of chloroauric acid trihydrate is 22.6 mM, and the concentration of chloropalladic acid is 22.6 mM) dropwise to the above solution and react for 1 hour, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone 7 times (alternating washing is centrifugal washing, the rotation speed is 8000 rpm, and the centrifugation time is 5 min) to obtain a washed product;
[0058] Subsequently, the washed product was further washed three times with 40°C warm water (also centrifugal washing) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst. The purified catalyst was dried in a vacuum drying oven at 40°C for 12 hours to obtain a gold-palladium catalyst, recorded as Au1@Pd1 catalyst.
[0059] 40 mg of the catalyst prepared in this example was mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, 3006 μL in total) to prepare catalyst ink. 300 μL of the catalyst ink was evenly coated on carbon paper (the actual coating area was 2×2 cm 2 ), vacuum dried at 40°C for 3h, and the catalyst-loaded carbon paper was obtained after drying, which was used as the working electrode for the electrocatalytic oxidation reaction of glycerol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, and the electrolyte was a mixed solution of glycerol and potassium hydroxide, totaling 60mL, in which the concentration of glycerol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 0.93V vs RHE, and the reaction time was 8h at room temperature and pressure.
[0060] The product was tested by high performance liquid chromatography and found that the glycerol conversion rate was 14% and the glyceric acid selectivity was 17%. Figure 5 shown.
[0061] Example 7: An anode catalyst for preparing glyceric acid by electrocatalytic oxidation of glycerol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 0:1:1.
[0062] Weigh 0.6 g of polyvinyl pyrrolidone, 3 g of ascorbic acid and 3 g of potassium bromide, stir and dissolve in 100 mL of ethylene glycol, stir and heat to 80° C.; then add 24 mL of copper sulfate pentahydrate aqueous solution (11.3 mM), continue heating and stirring for 0.5 h, then measure 12 mL of chloropalladic acid aqueous solution (22.6 mM) and dropwise add it to the above solution. After reacting for 1 h, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone for 7 times (alternating washing is centrifugal washing, the speed is 8000 rpm, and the centrifugation time is 5 min) to obtain the washed product;
[0063] Subsequently, the washed product was further washed three times with 40°C warm water (also centrifugal washing, rotation speed 8000rpm, centrifugal time 5min) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst. The purified catalyst was dried in a vacuum drying oven at 40°C for 12h to obtain a palladium copper catalyst, recorded as Pd1Cu1 catalyst.
[0064] 40 mg of the catalyst prepared in this example was mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, 3006 μL in total) to prepare catalyst ink. 300 μL of the catalyst ink was evenly coated on carbon paper (the actual coating area was 2×2 cm 2 ), vacuum dried at 40°C for 3h, and the catalyst-loaded carbon paper was obtained after drying, which was used as the working electrode for the electrocatalytic oxidation reaction of glycerol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, and the electrolyte was a mixed solution of glycerol and potassium hydroxide, totaling 60mL, in which the concentration of glycerol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 0.93V vs RHE, and the reaction time was 8h at room temperature and pressure.
[0065] The product was detected by high performance liquid chromatography and the glycerol conversion rate was 16% and the glyceric acid selectivity was 40%. The conversion rate and product distribution are shown in Figure 2. Figure 5 shown.
[0066] Example 8: An anode catalyst for preparing glyceric acid by electrocatalytic oxidation of glycerol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 1:0:1.
[0067] Weigh 0.6 g of polyvinyl pyrrolidone, 3 g of ascorbic acid and 3 g of potassium bromide, stir and dissolve in 100 mL of ethylene glycol, stir and heat to 80° C.; then add 24 mL of a cupric sulfate pentahydrate aqueous solution (11.3 mM), continue heating and stirring for 0.5 h, then measure 12 mL of a trihydrate chloroauric acid aqueous solution (22.6 mM) and dropwise add it to the above solution. After reacting for 1 h, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone for 7 times (alternating washing is centrifugal washing, with a rotation speed of 8000 rpm and a centrifugal time of 5 min) to obtain a washed product;
[0068] Subsequently, the washed product was further washed three times with 40°C warm water (also centrifugal washing) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst. The purified catalyst was dried in a vacuum drying oven at 40°C for 12 hours to obtain a gold-copper catalyst, recorded as Au1Cu1 catalyst.
[0069] 40 mg of the catalyst prepared in this example was mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, a total of 3006 μL) to prepare catalyst ink. 300 μL of the catalyst ink was evenly coated on carbon paper (the actual coating area was 2×2 cm 2 ), vacuum dried at 40°C for 3h, and the catalyst-loaded carbon paper was obtained after drying, which was used as the working electrode for the electrocatalytic oxidation reaction of glycerol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, and the electrolyte was a mixed solution of glycerol and potassium hydroxide, totaling 60mL, in which the concentration of glycerol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 0.93V vs RHE, and the reaction time was 8h at room temperature and pressure.
[0070] The catalyst prepared in this example was used as an anode electrocatalyst and evenly dropped on carbon paper. The mixture was vacuum dried at 40°C for 3 h to obtain carbon paper loaded with the catalyst, which was used as a working electrode for the electrocatalytic oxidation reaction of glycerol. Mercury-mercuric oxide was used as a reference electrode and a carbon rod was used as a counter electrode. The electrolyte was a mixed solution of 0.1 mol / L glycerol and 1 mol / L potassium hydroxide, totaling 60 mL. The applied potential was set to 0.93 V vs RHE. The reaction time was 8 h at room temperature and pressure.
[0071] The product was detected by high performance liquid chromatography and the glycerol conversion rate was 12% and the glyceric acid selectivity was 11%. The conversion rate and product distribution were as follows: Figure 5 shown.
[0072] Example 9: An anode catalyst for preparing glyceric acid by electrocatalytic oxidation of glycerol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 1:1:1.
[0073] The preparation method of the above catalyst specifically comprises the following steps: weighing 0.6g polyvinyl pyrrolidone, 3g ascorbic acid and 3g potassium bromide, stirring and dissolving them in 100mL ethylene glycol, stirring and heating to 80°C; then measuring 24mL of copper sulfate pentahydrate aqueous solution (11.3mM) and adding it to the ethylene glycol solution, continuing heating and stirring for 0.5h, then measuring 12mL of a mixed solution of chloroauric acid trihydrate and chloropalladic acid (in the mixed solution, the concentration of chloroauric acid trihydrate is 22.6mM, and the concentration of chloropalladic acid is 22.6mM) and adding it dropwise to the above solution to react for 1h, collecting the product by centrifugation, and washing the obtained product alternately with anhydrous ethanol and acetone 7 times (alternating washing is centrifugal washing, with a rotation speed of 8000rpm and a centrifugal time of 5min) to obtain a washed product;
[0074] Subsequently, the washed product was further washed three times with 40°C warm water (also centrifugal washing) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst. The purified catalyst was dried in a vacuum drying oven at 40°C for 12 hours to obtain a gold palladium copper catalyst, recorded as Au1@Pd1Cu1 catalyst.
[0075] 40 mg of the catalyst prepared in this example was mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, a total of 3006 μL) to prepare catalyst ink. 300 μL of the catalyst ink was evenly coated on carbon paper (the actual coating area was 2×2 cm 2 ), vacuum dried at 40°C for 3h, and the catalyst-loaded carbon paper was obtained after drying, which was used as the working electrode for the electrocatalytic oxidation reaction of glycerol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, and the electrolyte was a mixed solution of glycerol and potassium hydroxide, totaling 60mL, in which the concentration of glycerol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 0.83V vs RHE, and the reaction time was 8h at room temperature and pressure.
[0076] The product was detected by high performance liquid chromatography and found that the glycerol conversion rate was 50% and the glyceric acid selectivity was 39%;
[0077] The conversion rate and product distribution are as follows Figure 6 shown.
[0078] Example 10: An anode catalyst for preparing glyceric acid by electrocatalytic oxidation of glycerol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 1:1:1.
[0079] Weigh 0.6 g of polyvinyl pyrrolidone, 3 g of ascorbic acid and 3 g of potassium bromide, stir and dissolve in 100 mL of ethylene glycol, stir and heat to 80° C.; then add 24 mL of a cupric sulfate pentahydrate aqueous solution (11.3 mM), continue heating and stirring for 0.5 h, then measure 12 mL of a mixed solution of chloroauric acid trihydrate and chloropalladic acid (in the mixed solution, the concentration of chloroauric acid trihydrate is 22.6 mM, and the concentration of chloropalladic acid is 22.6 mM) and add dropwise to the above solution to react for 1 h, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone 7 times (alternating washing is centrifugal washing, the speed is 8000 rpm, and the centrifugation time is 5 min) to obtain the washed product;
[0080] Subsequently, the washed product was further washed three times with 40°C warm water (also centrifugal washing) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst. The purified catalyst was dried in a vacuum drying oven at 40°C for 12 hours to obtain a gold palladium copper catalyst, recorded as Au1@Pd1Cu1 catalyst.
[0081] 40 mg of the catalyst prepared in this example was mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, a total of 3006 μL) to prepare catalyst ink. 300 μL of the catalyst ink was evenly coated on carbon paper (the actual coating area was 2×2 cm 2 ), vacuum dried at 40°C for 3h, and the catalyst-loaded carbon paper was obtained after drying, which was used as the working electrode for the electrocatalytic oxidation reaction of glycerol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, and the electrolyte was a mixed solution of glycerol and potassium hydroxide, totaling 60mL, in which the concentration of glycerol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 0.88V vs RHE, and the reaction time was 8h at room temperature and pressure.
[0082] The product was detected by high performance liquid chromatography and found that the glycerol conversion rate was 55% and the glyceric acid selectivity was 35%.
[0083] The conversion rate and product distribution are as follows Figure 6 shown.
[0084] Example 11: An anode catalyst for preparing glyceric acid by electrocatalytic oxidation of glycerol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 1:1:1.
[0085] Weigh 0.6 g of polyvinyl pyrrolidone, 3 g of ascorbic acid and 3 g of potassium bromide, stir and dissolve in 100 mL of ethylene glycol, stir and heat to 80° C.; then add 24 mL of a cupric sulfate pentahydrate aqueous solution (11.3 mM), continue heating and stirring for 0.5 h, then measure 12 mL of a mixed solution of chloroauric acid trihydrate and chloropalladic acid (in the mixed solution, the concentration of chloroauric acid trihydrate is 22.6 mM, and the concentration of chloropalladic acid is 22.6 mM) and add dropwise to the above solution to react for 1 h, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone 7 times (alternating washing is centrifugal washing, the speed is 8000 rpm, and the centrifugation time is 5 min) to obtain the washed product;
[0086] Subsequently, the washed product was further washed three times with 40°C warm water (also centrifugal washing) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst. The purified catalyst was dried in a vacuum drying oven at 40°C for 12 hours to obtain a gold palladium copper catalyst, recorded as Au1@Pd1Cu1 catalyst.
[0087] 40 mg of the catalyst prepared in this example was mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, a total of 3006 μL) to prepare catalyst ink. 300 μL of the catalyst ink was evenly coated on carbon paper (the actual coating area was 2×2 cm 2 ), vacuum dried at 40°C for 3h, and the catalyst-loaded carbon paper was obtained after drying, which was used as the working electrode for the electrocatalytic oxidation reaction of glycerol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, and the electrolyte was a mixed solution of glycerol and potassium hydroxide, totaling 60mL, in which the concentration of glycerol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 0.98V vs RHE, and the reaction time was 8h at room temperature and pressure.
[0088] The product was detected by high performance liquid chromatography and found that the glycerol conversion rate was 50% and the glyceric acid selectivity was 31%;
[0089] The conversion rate and product distribution are as follows Figure 6 shown.
[0090] Example 12: An anode catalyst for preparing glyceric acid by electrocatalytic oxidation of glycerol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 1:1:1.
[0091] Weigh 0.6g of polyvinyl pyrrolidone, 3g of ascorbic acid and 3g of potassium bromide, stir and dissolve in 100mL of ethylene glycol, stir and heat to 80°C; then measure 24mL of copper sulfate pentahydrate aqueous solution (11.3mM) and add it to the ethylene glycol solution, continue heating and stirring for 0.5h, then measure 12mL of a mixed solution of chloroauric acid trihydrate and chloropalladic acid (in the mixed solution, the concentration of chloroauric acid trihydrate is 22.6mM, and the concentration of chloropalladic acid is 22.6mM) and add it dropwise to the above solution to react for 1h, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone 7 times (alternating washing is centrifugal washing, the speed is 8000rpm, and the centrifugation time is 5min) to obtain the washed product;
[0092] Subsequently, the washed product was further washed three times with 40°C warm water (centrifugal washing, rotation speed 8000rpm, centrifugal time 5min) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst. The purified catalyst was dried in a vacuum drying oven at 40°C for 12h to obtain a gold palladium copper catalyst, recorded as Au1@Pd1Cu1 catalyst.
[0093] 40 mg of the catalyst prepared in this example was mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, a total of 3006 μL) to prepare catalyst ink. 300 μL of the catalyst ink was evenly coated on carbon paper (the actual coating area was 2×2 cm 2 ), vacuum dried at 40°C for 3h, and the catalyst-loaded carbon paper was obtained after drying, which was used as the working electrode for the electrocatalytic oxidation reaction of glycerol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, and the electrolyte was a mixed solution of glycerol and potassium hydroxide, totaling 60mL, in which the concentration of glycerol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 1.03V vs RHE, and the reaction time was 8h at room temperature and pressure.
[0094] The product was detected by high performance liquid chromatography and the glycerol conversion rate was 8% and the glyceric acid selectivity was 38%. The conversion rate and product distribution were as follows: Figure 6 shown.
[0095] Example 13: An anode catalyst for preparing glyceric acid by electrocatalytic oxidation of glycerol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 1:1:1.
[0096] Weigh 0.6g of polyvinyl pyrrolidone, 3g of ascorbic acid and 3g of potassium bromide, stir and dissolve in 100mL of ethylene glycol, stir and heat to 80°C; then measure 24mL of copper sulfate pentahydrate aqueous solution (11.3mM) and add it to the ethylene glycol solution, continue heating and stirring for 0.5h, then measure 12mL of a mixed solution of chloroauric acid trihydrate and chloropalladic acid (in the mixed solution, the concentration of chloroauric acid trihydrate is 22.6mM, and the concentration of chloropalladic acid is 22.6mM) and add it dropwise to the above solution to react for 1h, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone 7 times (alternating washing is centrifugal washing, the speed is 8000rpm, and the centrifugation time is 5min) to obtain the washed product;
[0097] Subsequently, the washed product was further washed three times with 40°C warm water (centrifugal washing, rotation speed 8000rpm, centrifugal time 5min) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst. The purified catalyst was dried in a vacuum drying oven at 40°C for 12h to obtain a gold palladium copper catalyst, recorded as Au1@Pd1Cu1 catalyst.
[0098] 40 mg of the catalyst prepared in this example was mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, a total of 3006 μL) to prepare catalyst ink. 300 μL of the catalyst ink was evenly coated on carbon paper (the actual coating area was 2×2 cm 2 ), vacuum dried at 40°C for 3h, and the catalyst-loaded carbon paper was obtained after drying, which was used as the working electrode for the electrocatalytic oxidation reaction of glycerol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, and the electrolyte was a mixed solution of glycerol and potassium hydroxide, a total of 60mL, in which the concentration of glycerol was 0.1mol / L, and the concentration of potassium hydroxide was 1mol / L; the applied potential was set to 0.93V vs RHE, and the reaction time was 16h at room temperature and pressure.
[0099] The product was detected by high performance liquid chromatography and the glycerol conversion rate was 73% and the glyceric acid selectivity was 34%. The conversion rate and product distribution are shown in Figure 2. Figure 7 shown.
[0100] Example 14: An anode catalyst for preparing glyceric acid by electrocatalytic oxidation of glycerol, wherein the atomic ratio of gold, palladium and copper in the gold-palladium-copper catalyst is 1:1:1.
[0101] Weigh 0.6 g of polyvinyl pyrrolidone, 3 g of ascorbic acid and 3 g of potassium bromide, stir and dissolve in 100 mL of ethylene glycol, stir and heat to 80° C.; then add 24 mL of a cupric sulfate pentahydrate aqueous solution (11.3 mM), continue heating and stirring for 0.5 h, then measure 12 mL of a mixed solution of chloroauric acid trihydrate and chloropalladic acid (in the mixed solution, the concentration of chloroauric acid trihydrate is 22.6 mM, and the concentration of chloropalladic acid is 22.6 mM) and add dropwise to the above solution to react for 1 h, collect the product by centrifugation, and wash the obtained product alternately with anhydrous ethanol and acetone 7 times (alternating washing is centrifugal washing, the speed is 8000 rpm, and the centrifugation time is 5 min) to obtain the washed product;
[0102] Subsequently, the washed product was further washed three times with 40°C warm water (also centrifugal washing) to completely remove the polyvinyl pyrrolidone in the catalyst to obtain a purified catalyst. The purified catalyst was dried in a vacuum drying oven at 40°C for 12 hours to obtain a gold palladium copper catalyst, recorded as Au1@Pd1Cu1 catalyst.
[0103] 40 mg of the catalyst prepared in this example was mixed with deionized water, isopropanol, ethylene glycol and Nafion solution (v:v:v:v=20:5:3:2, a total of 3006 μL) to prepare catalyst ink. 300 μL of the catalyst ink was evenly coated on carbon paper (the actual coating area was 2×2 cm 2 ), vacuum dried at 40°C for 3h, and the catalyst-loaded carbon paper was obtained after drying, which was used as the working electrode for the electrocatalytic oxidation reaction of glycerol. Mercury-mercuric oxide was used as the reference electrode, the carbon rod was used as the counter electrode, and the electrolyte was a mixed solution of glycerol and potassium hydroxide, totaling 60mL, in which the concentration of glycerol was 0.1mol / L, and the concentration of potassium hydroxide was 0.1mol / L. The applied potential was set to 0.93Vvs RHE, and the reaction time was 8h at room temperature and pressure.
[0104] The product was detected by high performance liquid chromatography and found that the glycerol conversion rate was 9% and the glyceric acid selectivity was 52%;
[0105] Figure 2-3 The XRD patterns and CV patterns of the catalysts prepared in Examples 1 and 4-8 show that the catalyst Au1@Pd1Cu1 has the lowest overpotential under the same conditions and the highest current density at 0.93 V vs RHE.
[0106] Figure 4This is a graph showing the relationship between product selectivity and substrate conversion when the prepared catalyst in Example 1-3 is reacted for 8 hours at an applied potential of 0.93 V. It can be seen from the graph that the catalyst Au1@Pd1Cu1 is universal for the oxidation of biomass alcohols, with a glycerol conversion rate of 59%, a 1,2-propylene glycol conversion rate of 51%, and an ethylene glycol conversion rate of 72%.
[0107] Figure 5 The relationship diagram between product selectivity and glycerol conversion rate of the catalysts prepared in Examples 1 and 4-8 when the applied potential was 0.93 V and the reaction was carried out for 8 hours. Under the same reaction time, the Au1@Pd1Cu1 catalyst has the highest glycerol conversion rate (59%) and moderate glyceric acid selectivity.
[0108] Figure 6 The glycerol conversion rate and product selectivity distribution diagram of the catalyst prepared in Examples 1 and 9-12 at different reaction potentials. It can be seen from the figure that as the reaction potential gradually increases to 0.93V, the highest glycerol conversion rate is achieved. When the potential rises to 1.03V, although the glyceric acid selectivity is higher than 0.93V, the glycerol conversion rate decreases significantly. Considering all factors, the optimal reaction potential is selected to be 0.93V.
[0109] Figure 7 The glycerol conversion rate and product selectivity distribution diagram of the catalyst prepared in Examples 1 and 13 at an applied potential of 0.93 V at different reaction times. It can be seen from the figure that with the increase of reaction time, the glycerol conversion rate increases, but the glycerol selectivity does not change significantly.
[0110] Based on the above results, the optimal atomic ratio of gold, palladium and copper in the catalyst is 1:1:1, because it has the highest glycerol conversion rate and moderate glyceric acid selectivity; combined with the results of Examples 1 and 9-12, the optimal reaction potential is 0.93 V, at which the catalyst has the highest glycerol conversion rate and a glyceric acid selectivity that is basically the same as other potentials.
[0111] In summary, the optimal atomic ratio of gold, palladium and copper is 1:1:1. When a mixed solution of 0.1 mol / L glycerol and 1 mol / L potassium hydroxide is used as the electrolyte, the potential is applied at 0.93 V for 8 hours, the glycerol conversion rate is 59%, and the glyceric acid selectivity is 34%; after adjusting the electrolyte to a mixed solution of 0.1 mol / glycerol and 1 mol / L potassium hydroxide, the potential is applied at 0.93 V for 8 hours, and the glyceric acid selectivity will be increased to 52%; when a mixed solution of 0.1 mol / L 1,2-propylene glycol and 1 mol / L potassium hydroxide is used as the electrolyte, the potential is applied at 0.93 V for 8 hours, the 1,2-propylene glycol conversion rate is 51%, and the lactic acid selectivity is 53%; when a mixed solution of 0.1 mol / L ethylene glycol and 1 mol / L potassium hydroxide is used as the electrolyte, the potential is applied at 0.93 V for 8 hours, the ethylene glycol conversion rate is 72%, and the glycolic acid selectivity is 99%.
[0112] The reaction principle of the present invention is:
[0113] The anode reaction of glycerol oxidation is: C3H8O3+4OH - →C3H6O4(GLA)+3H2O+4e - ; The cathode reaction is: 4H2O+4e - →2H2+4OH - ; The overall reaction is: C3H8O3+H2O→C3H6O4(GLA)+2H2;
[0114] The anode reaction of 1,2-propylene glycol is: C3H8O2+4OH - →C3H6O3(LA)+3H2O+4e - ; The cathode reaction is: 4H2O+4e - →2H2+4OH - ; The overall reaction is: C3H8O3+H2O→C3H6O4(LA)+2H2;
[0115] The anode reaction of ethylene glycol is: C2H6O2+4OH - →C2H4O3(GCA)+3H2O+4e - ; The cathode reaction is: 4H2O+4e - →2H2+4OH - ;The overall reaction is: C2H6O2+H2O→C2H4O3(GCA)+2H2.
[0116] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. An electrocatalyst, characterized in that The electrocatalyst is a gold-palladium-copper ternary metal electrocatalyst, which is composed of gold, palladium and copper, wherein palladium is an active component, gold is a core and palladium-copper alloy is a shell of a core-shell structure; the molar ratio of gold, palladium and copper in the catalyst is 1:1:
1.
2. The method for preparing an electrocatalyst according to claim 1, characterized in that: Add polyvinyl pyrrolidone, ascorbic acid and potassium bromide to ethylene glycol, stir and heat to a certain temperature, then drop a pentahydrate copper sulfate aqueous solution, react for a period of time after the dropwise addition, and then drop a mixed solution A to continue the reaction, wherein the mixed solution A is a mixed solution of trihydrate chloroauric acid and chloropalladic acid; after the reaction, stop stirring and cool naturally to room temperature, collect the product by centrifugation or filtration, and wash the obtained product with anhydrous ethanol and acetone alternately for several times to obtain a washed product; Subsequently, the washed product is further washed with warm water for several times, and the product obtained after washing is a purified catalyst; finally, the purified catalyst is dried to obtain a gold-palladium-copper catalyst; wherein, chloropalladic acid is prepared by mixing palladium chloride and concentrated hydrochloric acid in a molar ratio of 1:
2.
3. The method for preparing an electrocatalyst according to claim 2, characterized in that: The dosage relationship of the ethylene glycol, polyvinyl pyrrolidone, ascorbic acid, potassium bromide, copper sulfate pentahydrate aqueous solution, and mixed solution A is 50-100 mL: 0.3-0.6 g: 2-4 g: 2-4 g: 12-24 mL: 12-24 mL; wherein the concentration of copper sulfate pentahydrate aqueous solution is 11.3 mM; the concentration of chloroauric acid trihydrate in mixed solution A is 22.6 mM, and the concentration of chloropalladic acid is 22.6 mM.
4. The method for preparing an electrocatalyst according to claim 2, characterized in that: The temperature is raised to 70-90° C., and then copper sulfate pentahydrate aqueous solution is added dropwise to react for 0.5-1 h. The mixed solution A is added dropwise to continue the reaction for 1-2 h.
5. The method for preparing an electrocatalyst according to claim 2, characterized in that: The alternating washing is performed 7-8 times, and the washing operation is centrifugal washing, with a rotation speed of 8000-10000 rpm and a centrifugal time of 3-5 minutes.
6. The method for preparing an electrocatalyst according to claim 1, characterized in that: The temperature of the warm water is 40° C., the washing is continued for 3 times, the washing operation is centrifugal washing, the rotation speed is 8000-10000 rpm, and the centrifugal time is 3-5 minutes.
7. Use of the electrocatalyst according to claim 1 or the electrocatalyst prepared by the method according to claim 2-6 for oxidation of terminal hydroxyl groups of biomass alcohols.
8. The use according to claim 7, characterized in that The steps are as follows: evenly mixing a gold palladium copper catalyst with deionized water, isopropanol, ethylene glycol and Nafion solution to obtain a catalyst ink; then evenly coating the catalyst ink on carbon paper, and vacuum drying to obtain the carbon paper loaded with the gold palladium copper catalyst; at room temperature and pressure, using the carbon paper loaded with the gold palladium copper catalyst as a working electrode, a mercury-mercuric oxide electrode as a reference electrode, and a carbon rod as a counter electrode to form a three-electrode system, using an anion exchange membrane to separate the positive and negative electrodes, the entire reaction environment is carried out in a saturated nitrogen atmosphere, and an electrochemical workstation is used to apply a constant potential to the electrolyte to achieve the purpose of oxidizing the terminal hydroxyl groups of biomass alcohol; the electrolyte is a mixed solution of glycerol and potassium hydroxide, a mixed solution of 1,2-propylene glycol and potassium hydroxide, or a mixed solution of ethylene glycol and potassium hydroxide.
9. The use according to claim 8, characterized in that The dosage ratio of the gold palladium copper catalyst to isopropanol is 40 mg:501 μL; the volume ratio of the deionized water, isopropanol, ethylene glycol and Nafion solution is 20:5:3:2; the dosage relationship of the catalyst ink and carbon paper is: 70-75 μL per square centimeter of carbon paper; the vacuum drying temperature is 40-60°C, and the drying time is 3-4 hours.
10. The use according to claim 8, wherein in the mixed solution of glycerol and potassium hydroxide, the molar ratio of glycerol to potassium hydroxide is 0.05-0.5 mol:0.5-2 mol; in the mixed solution of 1,2-propylene glycol and potassium hydroxide, the molar ratio of 1,2-propylene glycol to potassium hydroxide is 0.05-0.5 mol:0.5-2 mol; in the mixed solution of ethylene glycol and potassium hydroxide, the molar ratio of ethylene glycol to potassium hydroxide is 0.05-0.5 mol:0.5-2 mol; the flow rate of nitrogen is 100 mL / min, and the applied constant potential is 0.83-1.03 V.